Sosialisasi Pembuatan Komposit Berbahan Kuningan Dan Serbuk Jati Untuk Kampas Rem Sepeda Motor Di Perumahan Baladewa Baregbeg - Gugun Gundara; Muhammad Hisyam (Universitas Muhammadiyah Tasikmalaya, 2023)
The brake camp is one of the components available on a motorcycle that works to slow or stop the speed of the vehicle especially at high speed so that it has an impact on the safety of the driver.Therefore it must be made of materials that not only produce large friction. But it should also be resistant to friction and does not produce heat that can cause the material to melt or change shape.The material is gloves and powders.The material is easy to obtain so that society does not have trouble looking for the material.This activity aims to introduce to the public that motorcycle brake camps can be made with materials from gloves or dust. methods used in the form of lectures and demonstrations.The results of this activity are interested in the public and are willing to try the production of compound brake camps from gloves and gloves powder.